The origin and localization of "vermiculite" along the intra‐terrane shear zones in the Bundelkhand Craton, India: Mechanism and implication. Issue 10 (9th June 2022) - Banerjee, Sayandeep; Maity, Sayan; Sarkar, Goutam; Acharya, Shriza
Abstract : Vermiculite, a clay mineral of economic importance, is reported for the first time from the Bundelkhand Craton. The locales of the vermiculite occurrence are mapped within the Bundelkhand granitoids at several places. The identification of the fracture system and the zones of strain localization within Bundelkhand granitoids are critical for targeting the occurrences of vermiculite. A range of studies including meso‐, micro‐, and sub‐microscopic analyses were used to delineate the characteristic features of vermiculite along the brittle/ductile shear zones in the Bundelkhand Craton. SEM‐based EDS, EPMA, and XRD analyses confirm the ubiquitous dominance of vermiculite as fracture infills and/or channel infill materials along the zones of nucleation of ductile shear zones. It is postulated here that the occurrence of vermiculite is a result of supergene alteration of biotite present in the vein material. The parent material of the fracture infills from which the veins crystallized is genetically derived from the host rock (Bundelkhand granitoid), which later healed the fractures and prompted the nucleation of ductile shear zones in the Bundelkhand Craton. Abstract : Highlights: The article presents the first report of occurrences of vermiculite in the BundelkhandCraton. Vermiculite, aclay mineral of economic importance. The article emphasizes on the origin andlocalization of vermiculite along the ductile shear zones of the craton. The article illustrates the role of vermiculite in transforming theprecursor brittle fractures into the sites of ductile shear zone in the Bundelkhand granitoid.